Baculovirus Surface Display Using Infuenza Neuraminidase (NA) Transmembrane Anchor - Irisa Trianti; Saengchai Akeprathumchai; Phenjun Mekvichitsaeng; Kanokwan Poomputsa (Journal of Tropical Life Science, 2016)
Baculovirus surface display has been employed as an excellent tools for presentation of foreign peptides and proteins on virus surface with native conformation, functions and immunogenicity. A baculovirus major envelope protein, gp64, or a capsid protein, vp39 are generally used as fusion partners for displaying of polypeptides on the surface of virions. Alternatively, a membrane anchoring domain of vesicular stomatitis virus G protein (VSV-G) can also be used. In this study, an influenza neuraminidase (NA) was proposed as a new membrane anchor for the display of Angiotensin II (AngII), DRVYIHPFHL, peptides. The AngII peptides were inserted into NA by replacing NA amino acid number 60-67 with AngII, and then integrated into a baculovirus genome. A recombinant baculovirus expressing the NA fusion-AngII peptides was generated from infected insect cells. Those peptides were found to express and translocated on the membrane of the baculovirus infected insect cell (Sf9 cell) as detected by immunocytochemistry using anti-AngII monoclonal antibody. Upon budding of the recombinant baculovirus progenies through the insect cells membrane, the recombinant NA-AngII peptides was acquired to envelopes of the new baculovirus progenies. The conformation of NA on baculovirus surface was not affected by the deletion, as the 55 kDa band of NA can be detected from Western Blotting analysis by specific anti-NA monoclonal antibody. In addition, the same protein was also found by anti-AngII antibody indicating that the AngII peptides had been successfully fused with the recombinant NA. Interestingly, electron microscopy analysis demonstrated that not only the recombinant baculovirus displaying AngII peptides were generated by infected insect cells, but also the NA virus-like-particle displaying AngII peptides.